Cell Analysis on Microfluidics (Integrated Analytical Systems,, 2018)
This book presents a detailed overview of the design, formatting, application, and development of microfluidic chips in the context of cell biology research, enumerating each element involved in microfluidics-based cell analysis, discussing its history, status quo, and future prospects, It also offers an extensive review of the research completed in the past decade, including numerous color figures. The individual chapters are based on the respective authors' studies and experiences, providing tips from the frontline to help researchers overcome bottlenecks in their own work. It highlights a number of cutting-edge techniques, such as 3D cell culture, microfluidic droplet technique, and microfluidic chip-mass spectrometry interfaces, offering a first-hand impression of the latest trends in the field and suggesting new research directions. Serving as both an elementary introduction and advanced guidebook, the book interests and inspires scholars and students who are currently studying microfluidics-based cell analysis methods as well as those who wish to do so.